Chemical variability and evaluation of physical parameters of the essential oil of the leaves of Casearia sylvestris varieties and morphoanatomical characterization of the leaves - Carvalho, Flávio A. [UNESP]; Oda, Fernando B. [UNESP]; Sacramento, Luis V. S. [UNESP]; Pereira, Fabíola M. V. [UNESP]; Crevelin, Eduardo J.; Crotti, Antônio E. M.; Santos, André G. [UNESP] (My University, 2023)
Casearia sylvestris Swartz is a traditional medicinal plant classified into the ‘sylvestris’ and ‘lingua’ varieties. The essential oil (EO) of the leaves showed anti-inflammatory, antiulcerogenic, cytotoxicity, antimicrobial, and antileishmanial activities. Studying the chemical variability of this EO is important to establish its quality specifications and standardization. Here, we evaluated the population, seasonal, and circadian chemical composition of the EO of C. sylvestris varieties, the morphoanatomical characteristics of C. sylvestris leaves, and the physical parameters of the EO. Gas chromatography–mass spectrometry (GC–MS) and principal component analysis (PCA) were used to assess the metabolic profile of the EO of C. sylvestris varieties. The main compounds in the EO were β-elemene, α-humulene (2), germacrene D (3), bicyclogermacrene (4), spathulenol (5), caryophyllene oxide, and humulene epoxide II. Population, intrapopulation, seasonal, and circadian chemical variability was verified. Higher contents of germacrene D (3), α-muurolol, and α-cadinol differentiated the EO of the ‘lingua’ variety from the EO of the ‘sylvestris’ variety. The optical rotation of the EO of the ‘lingua’ and ‘sylvestris’ varieties ranged from − 99.5 to − 98.7° and from + 82.3 to + 190.1°, respectively, whilst the EO of these varieties had the same refractive index (1.500) and density (0.922 g/mL). The ‘lingua’ and ‘sylvestris’ varieties presented trunk fissures of 5.0 and 0.5 cm, respectively. The palisade index was 2.9 for ‘lingua’ and 3.9–4.3 for ‘sylvestris’. The leaves were amphistomatic in ‘lingua’ and hypostomatic in ‘sylvestris’. Graphical abstract: [Figure not available: see fulltext.].
Keywords: Chemical variability; Circadian; Palisade index; Principal component analysis; Seasonal analysis; Sesquiterpenes